2018
DOI: 10.1093/carcin/bgy091
|View full text |Cite
|
Sign up to set email alerts
|

Cell line-based xenograft mouse model of paediatric glioma stem cells mirrors the clinical course of the patient

Abstract: We have established a robust and reliable cell line-based glioma stem cell xenograft mouse model, genetically and epigenetically similar to its originating patient tumours. The survival of patients and injected mice correlate significantly, demonstrating that the transplanted mice mimic the clinical course of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Invasive growth and tumor recurrence are the two key characteristics of diffuse gliomas in humans. Invasive patient-derived orthotopic xenografts (PDOXs) for gliomas have been modeled from patient surgical specimens and patient-derived short-term cultures [11, 21, 22]. In addition, invasive orthotopic gliomas have been established from subcutaneous xenografts from surgical specimens of patients with gliomas and from their propagations [23].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive growth and tumor recurrence are the two key characteristics of diffuse gliomas in humans. Invasive patient-derived orthotopic xenografts (PDOXs) for gliomas have been modeled from patient surgical specimens and patient-derived short-term cultures [11, 21, 22]. In addition, invasive orthotopic gliomas have been established from subcutaneous xenografts from surgical specimens of patients with gliomas and from their propagations [23].…”
Section: Discussionmentioning
confidence: 99%
“…These wellcharacterised cells have been shown to be stable during culturing and maintain their DNA methylation profiles and DNA copy number alterations (CNA). The expression of stem cell proteins as well as in vivo tumour-initiating capacity of these cells [16] demonstrates their resemblance to cancer stem cells or progenitor cells. These cells hence provide a relevant and robust model system for functional studies on paediatric brain tumours.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of the perivascular niche in terms of the spread of glioma cells along the Scherer structures also seems to be possible in xenograft models. Cell-line-based orthotopic implantation of glioma stem cells into immunodeficient mice showed that the gliomas revealed the molecular biological characteristics of the donor gliomas and the tumors formed secondary structures, as described by Scherer in the sense of perivascular, perineuronal, and meningeal accumulation (Larsson et al, 2018). Humanized PDX models seem to have an advantage here, as the representation of Scherer structures/glioma niches could be examined in a (human) immunocompetent environment.…”
Section: The Niches In the Microenvironmentmentioning
confidence: 86%